A Study into the Adoption of Internet of Things – IoT Technologies within Contractors in Dubai, United Arab Emirates - Al-Amleh, Khalel (2020)
Purpose – The construction industry has remained conservative and lagged in the implementation of technology. Although the industry has a fragmented nature and plays a critical role in social and economic development, technology is adversely limited. Due to technology's role to improve productivity, save time, and enhance stakeholder satisfaction, the construction industry has an opportunity to improve its performance and safety. Thus, the purpose of this research is to investigate the adoption of the internet of things technologies within contracting organizations in the Emirate of Dubai. Methodology – Through a quantitative approach, a total of 116 construction professionals participated in a distributed online questionnaire. All the respondents were professional engineers with experience and knowledge of construction activities. Descriptive analysis using the Relative Importance Index - RII technique was used to rate the collected data according to respondents. Regression analysis was used to test the research hypotheses and Multiple linear regression was utilized to develop a prediction model. Findings – According to respondents, when asked on the types of IoT technologies utilized by their organizations BIM, smartphones, and cloud storage systems were the contractors' leading types of IoT technologies adopted. When tackling the areas of IoT technologies implementation, the top three areas were data exchange, data capturing & display and site supervision. All the studied internal and external factors promoting adoption were statistically significant when tested. The top three internal factors were communication, productivity, and management & procurement. The top three external factors were stakeholder satisfaction, competitive advantage, and government regulations. When challenges were tested for significance, three out of seven were statistically insignificant namely lack of leadership commitment, culture and resistance to change and connectivity issues. Currently, the leading challenges that must be addressed to promote adoption were the cost of implementation and staff training. When advantages were studied, the top three were enhanced communication, timesaving, and productivity. Research Limitations – The project focused on a small geographical area which is the Emirate of Dubai hence, it may lack generalizability. At the same time, a relatively small sample size (n=116) was used in the study. Besides, the project focused only on contractors in the construction industry. It is recommended that future researchers expand their studies' scope to evaluate IoT technologies in other parts of the country as well as the globe. Moreover, they should focus on other players in the construction industry, besides contractors. Theoretical Contributions – This research provides a never-done-before look at the current state of IoT technologies adoption within contractors in the Emirate of Dubai. The used methodology and developed model will enrich existing literature by providing a framework to help adopt IoT technologies within contracting organizations. The research helps bridge the gap in existing literature related to the role of IoT technologies within the construction sector in the Emirate of Dubai and understand how this adoption affected the sector. Practical Implications – From the research results, it was evident that contractors in Dubai are utilizing and relying on IoT technologies to enhance data collection and sharing, leading to improving their productivity and managing time and cost overruns. This research provides a practical guideline for willing contractors to embrace IoT technologies. Therefore, this research is of value not only to contracting organizations but rather to all organizations within the industry who are planning to adopt new technologies. Social Implications – For contractors willing to embrace IoT technologies, it is recommended that they start training their workforce on the use of IoT technologies and create partnerships to deal with cost challenges. If implemented, this would create new business opportunities and job vacancies that would affect multiple sectors within the economy.